Ketogenic diet, African American women, and cardiovascular health: A systematic review. Issue 1 (19th January 2022) - Hanners, Audra; Melnyk, Bernadette Mazurek; Volek, Jeff; Kelley, Marjorie M.
Abstract: Background: Cardiovascular disease (CVD) is the number one cause of death in the United States of America and across the world. The high prevalence of obesity (56.9%) in African American women contributes to high rates of CVD. Ketogenic nutritional therapy has been shown to be a safe and effective therapy for weight loss and reduction in other CVD risk factors (e.g., HgbA1C and blood pressure). However, the evidence investigating ketogenic nutritional therapy among African American women to improve CVD risk factors has not yet been synthesized. Aims: To conduct a systematic review of the evidence on CVD risk reduction and ketogenic nutrition therapy among African American women. Methods: CINAHL Plus, Cochrane, EMBASE, MEDLINE/PubMed, SCOPUS, and Web of Science were searched for quantitative studies focused on ketogenic nutritional therapy and CVD risk factors among African American women. Included studies measured beta‐hydroxybutyrate as an indicator of dietary adherence. Results: Of 4, 799 articles identified, six articles representing five studies were included in this review. The majority of participants were female, with very few identified as African American women. Primary outcomes included weight, body mass index (BMI), blood pressure, and lipids. Dietary adherence was difficult to assess. Significant reductions in weight and BMI were noted. Heterogeneity in study design, intervention length, and measurement of dietary adherence made generalizations difficult. Few studies continually monitored dietary adherence using beta‐hydroxybutyrate levels, thus threatening the internal validity of the studies. A gap in our understanding remains concerning CVD risk and ketogenic nutritional therapy among African American women specifically. Linking evidence to action: Ketogenic nutritional therapy is effective in women to reduce weight and BMI. Ketogenic nutritional therapy may be beneficial in reducing CVD risk factors. Monitoring dietary adherence using beta‐hydroxybutyrate levels with commercially available monitors is key to intervention success.